2020
DOI: 10.3389/fgene.2020.01030
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA AGAP2-AS1 Silencing Inhibits PDLIM5 Expression Impeding Prostate Cancer Progression via Up-Regulation of MicroRNA-195-5p

Abstract: Prostate cancer remains a significant cause of cancer-related deaths in male population. More recently, accumulating evidence continues to implicate long noncoding RNAs (lncRNAs), microRNAs (miRNAs), and mRNAs in various types of cancers, including prostate cancer. The current study aimed to elucidate the role of lncRNA AGAP2-AS1/miR-195-5p/PDZ and LIM domain 5 (PDLIM5) in prostate cancer progression. Initially, microarray expression profiles were applied to screen differentially expressed lncRNAs/miRNAs/genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…[49][50][51][52] High PDLIM5 expression in tumor tissues correlates with advanced PCa tumors in vivo. 53 We confirmed 35 out of 49 highly significant PCa susceptibility SNPs in Japanese, and 19 of them remained significant after stringent multiple testing adjustment. It appears that Taiwanese have fewer PCa susceptibility loci than Japanese.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[49][50][51][52] High PDLIM5 expression in tumor tissues correlates with advanced PCa tumors in vivo. 53 We confirmed 35 out of 49 highly significant PCa susceptibility SNPs in Japanese, and 19 of them remained significant after stringent multiple testing adjustment. It appears that Taiwanese have fewer PCa susceptibility loci than Japanese.…”
Section: Discussionsupporting
confidence: 59%
“…The oncogenic lncRNA AGAP2‐AS1, highly expressed in PCa, promotes PCa by binding to and inhibiting miR‐195‐5p, resulting in the upregulation of PDLIM5 and PCa progression. Silencing AGAP2‐AS1 leads to an upregulation of miR‐195‐5p and subsequent downregulation of PDLIM5 expression, resulting in the suppression of proliferation, migration, and invasion of PCa cells in vitro and the delayed growth of PCa tumors in vivo 53 …”
Section: Discussionmentioning
confidence: 99%
“…lncRNA ZFAS1 was reported to be a diagnosis feature in ESCC tissues [29]. Elevated lncRNA AGAP2-AS1 level was observed in prostate cancer [30]. The role of lncRNA HCG18 was previously reported to be a cancer-promoting gene, related to bladder cancer, papillary thyroid cancer, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xu et al found that PPARGC1B can alleviate IL-1β-mediated osteoarthritis [35]. If PDLIM5 is downregulated, some cancer progression rates will be suppressed [38]. More ceRNAregulated mechanisms need to be further explored and validated.…”
Section: Discussionmentioning
confidence: 99%